Benefits of Yin Yoga and Plank Exercise on Weight Loss in Overweight Adolescents - Jehaman, Isidorus; Yulianty, Monika; Karo-karo, Tati Murni; Harahap, Fitri Ramadhani (JURNAL PENGMAS KESTRA (JPK), 2023)
Background: Overweight is a physical condition caused by excessive accumulation of fat in the body due to an imbalance between food intake consumed and energy expended during bodily activities. Low physical activity has the potential to lead to obesity, especially when it starts as a child. The activities of children and adolescents are currently more playing gadgets and watching TV so that they have the potential to cause obesity. Overweight is a serious problem in Indonesia. This is because obesity will increase the risk of cardiovascular disease such as enlarged blood vessels, heart failure, stroke, fatty liver and hardening of the liver. Complications that can occur in overweight are heart attack, type II diabetes, stroke, hypertension, sleep apnea and breathing problems. To overcome the problematic consequences of being overweight are yin yoga and plank exercises. Yin yoga is currently one of the exercises that can reduce levels of fat in the body (burn bad calories in the body), relax the mind, and control breathing. Meanwhile, plank exercise is used to increase muscle strength. Plank movements help strengthen the muscles of the arms, shoulders, abdomen, legs, can also increase stability, and can burn up to 12 kcal of calories per round (healthy). This activity was carried out by physiotherapy students at the Lubuk Pakam Medistra Health Institute in the 2023 program with the aim of introducing the benefits of Yin yoga and plank exercises in overcoming and preventing the incidence of overweight among Physiotherapy students at the Lubuk Pakam Medistra Health Institute in 2023.